Mechanical Properties and Microstructural Characterization of Paper Produced from Rice Straw–Waste Paper Pulp Blends via Ethanol Organosolv Process - Aisyah Protonia Tanjung; Nadya Yunisa Fahmi; Dewi Fitria Marlisa; Maisarah; Lusyana Eka Wardani; Misbul Hadi; Rahmatun Maula (Jurnal Serambi Engineering, 2026)
The utilization of lignocellulosic agricultural waste as an alternative raw material for paper production offers a sustainable approach to reducing dependence on wood-based pulp. This study investigated the mechanical properties and microstructural characteristics of paper produced from blends of rice straw organosolv pulp and recycled waste paper pulp at a 1:1 ratio using 15 wt% polyvinyl acetate (PVAc) as binder. Sixteen paper samples were prepared under various ethanol concentrations (15–60 wt%) and cooking times (60–120 min). Mechanical characterization included tensile strength, elongation of break, and Young’s modulus, while surface morphology was analyzed using Scanning Electron Microscopy (SEM). The tensile strength ranged from 2.06 to 4.22 MPa, elongation of break from 6.00 to 16.06%, and Young’s modulus from 0.155 to 0.529 MPa. All samples satisfied the minimum tensile strength requirement of SNI 14-6519-2001. SEM observations revealed that higher tensile strength was associated with denser and more homogeneous fiber networks with fewer voids and surface defects. The optimum tensile strength was achieved at 30 wt% ethanol and 60 min cooking time, indicating favorable fiber bonding and structural integrity.